Identifying Commercial Sweet Spots: A Geomarketing Approach to Coffee Shop Spatial Competitiveness in Yogyakarta - Gulam Hazmin (Academic Bright Collaboration, 2026)
Purpose – This study maps coffee shop locations in the Yogyakarta–Sleman area to support evidence-based site selection for small businesses. It integrates competitor distribution and online customer-response data to identify areas with strong demand signals but relatively limited nearby competition. Methods – The study used 216 coffee shop POI records from Yogyakarta City and Sleman Regency. Geographic coordinates, ratings, and review counts were analyzed through competitor-radius counts, Kernel Density Estimation, Voronoi/grid-based logic, and a standardized sweet-spot score. Competitive pressure was measured using Haversine-distance buffers, while demand potential was proxied by rating multiplied by ln(1 + review count). Findings – Yogyakarta City was more saturated, with an average of 12.69 competitors within 1 km and 18.08 within 1.25 km per shop. Sleman showed lower local pressure, with 7.23 competitors within 1 km and 10.93 within 1.25 km. Ratings were nearly equivalent across areas, indicating that spatial exposure, rather than rating quality alone, better differentiates commercial opportunity. Correlation tests showed no statistically significant association between local competition and rating. Research implications – The framework provides business owners with a practical preliminary screening tool before conducting field surveys, lease negotiations, or financial planning. It also helps urban planners visualize business concentration and manage neighborhood commercial growth. Originality – The study proposes an integrated score combining online reviews, ratings, and local competition, while demonstrating that market crowding and customer-response strength should be assessed as separate decision layers.